2002
DOI: 10.2133/dmpk.17.348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Two Monkey Dihydrodiol Dehydrogenases

Abstract: Japanese monkey liver contains multiple forms of dihydrodiol dehydrogenase with 3(20)alpha-hydroxysteroid dehydrogenase activity. Here we have purified the major and minor forms (DD1 and DD4) of the enzyme from Cynomolgus monkey liver, and isolated cDNA species for the two enzyme forms by reverse transcription-PCR. The cDNAs encoded proteins comprising of 323 amino acids, in which the sequence identity between DD1 and DD4 was 83%. The sequences deduced from the cDNAs for DD1 and DD4 perfectly matched the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…A previous article from Higaki et al has reported expression of 20␣-HSD (DD1) in the liver, kidney, intestine, and adrenal gland, and of 3␣-HSD (DD4) in the liver and kidney of Japanese monkey tissues [17]. Those results are in agreement with our results, showing high expression levels of 20␣-HSD in the stomach, liver, kidney, and mammary gland and moderate levels in the ovary, adrenal, and colon.…”
Section: Discussionsupporting
confidence: 94%
“…A previous article from Higaki et al has reported expression of 20␣-HSD (DD1) in the liver, kidney, intestine, and adrenal gland, and of 3␣-HSD (DD4) in the liver and kidney of Japanese monkey tissues [17]. Those results are in agreement with our results, showing high expression levels of 20␣-HSD in the stomach, liver, kidney, and mammary gland and moderate levels in the ovary, adrenal, and colon.…”
Section: Discussionsupporting
confidence: 94%
“…While isatin and 5-bromoisatin were good substrates, 1-phenylisatin, a substrate of AKR1C18, 5) was not reduced. The enzyme showed less than 5% of the isatin reductase activity towards 1 mM of other a-dicarbonyl compounds (methylglyoxal, diacetyl and 3,4-hexanedione) and monocarbonyl compounds (4-nitrobenzaldehyde, pyridine-4-aldehyde, 4-nitroacetophenone, 4-benzoylpyridine), which are efficiently reduced by AKR1C18, 5) mouse 3(17)a-HSD (AKR1C21), 11) mouse 17b-HSD (AKR1C6), 12,13) AKR1C1, 14,15) and/or human 3a-HSDs (AKR1C2 and AKR1C4). 14,16) In this respect, AKR1C19 also differs from other members of the AKR superfamily such as aldehyde reductase, aldose reductase 17) and aflatoxin B1 aldehyde reductase 14) with broad substrate specificity for a variety of carbonyl compounds.…”
Section: )mentioning
confidence: 99%
“…1,[15][16][17] Mouse 3(17)a-HSDs were expected to be members of this family, because they also show high DD activity.…”
Section: Isolation Of Cdnas For Two Isoforms Of 3(17)a A-hsdmentioning
confidence: 99%